Assessment of left main coronary artery disease: a comparison between invasive and noninvasive. Issue 6 (22nd June 2022) - Alalawi, Luay H.; Dookhan, Christina M.; Verghese, Dhiran; Manubolu, Venkat S.; Aldana-Bitar, Jairo; Lakshmanan, Suvasini; Ahmad, Khadije; Shafter, Ahmad; Alchokhachi, Zahra; Ghanem, Ahmed; Golub, Ilana S.; Budoff, Matthew; et al.
Abstract : Left main coronary artery disease has significant therapeutic as well as prognostic implications. The presence of left main coronary artery stenosis is strongly associated with poor short- and long-term prognoses. Accurate identification of left main stenosis is extremely important since it would be the main factor to guide management. There are several modalities used to determine the presence of atherosclerosis and the degree of stenosis in a left main coronary artery. Newer modalities allow for an accurate evaluation of left main stenosis and atherosclerosis. In this review, we go through different invasive and noninvasive modalities to diagnose left main stenosis, shedding more light into coronary computed tomography angiography, and its accuracy in this specific diagnosis.